Adequação curricular: alternativas de suporte pedagógico na Educação Inclusiva - Leite, Lúcia Pereira [UNESP]; Martins, Sandra Eli Sartoreto de Oliveira [UNESP] (My University, 2010)
The organization of the inclusive education is a slow and complex process, which has the necessity of investments in supports for all the scholar team. Aiming at spreading one of the actions carried out for the promotion of the inclusive educational practices in a municipal education system in a western city in the state of São Paulo, this paperwork has the objective of presenting an elaborated manual of orientations for the implementation of the individual curricular adaptations (ACIs) for students who demand special educational necessities (NEEs). The material was constituted on the basis of three data sets: 1) tabulation of the evaluations of the curricular adaptations already made; 2) the literature review; 3) analysis of the themes which have emerged during case discussion meetings mediated by the researchers with teachers from the Specialized Pedagogical Support Service (SAPE), with teachers and administrators from the common education system and the technical-pedagogical team. The final version of the manual contemplates the theoretical-operational aspects about the themes: flexibility and curricular adequation, inclusive education, definitions of NEEs, how SAPE works; and it finishes with a model proposal of ACI. It is expected that the spreading of this material can subside new curricular propositions for students with deficiency that are very distant from the academic level expected for the current scholar year.

A organização da educação inclusiva é um processo lento e complexo, havendo a necessidade de investimentos em suportes para toda a equipe escolar. Visando divulgar uma das ações realizadas para a promoção de práticas educacionais inclusivas, numa rede municipal de ensino, de uma cidade do oeste paulista, este trabalho objetiva apresentar um manual elaborado para orientar os profissionais da educação na implementação das adequações curriculares individuais (ACIs) para alunos com necessidades educacionais especiais (NEEs). O material foi constituído com base em três conjuntos de dados: 1) tabulação da avaliação das adequações curriculares já efetivadas; 2) revisão da literatura; 3) análise de temáticas que emergiram em reuniões de discussão de caso mediadas pelas pesquisadoras com: professores do Serviço de Apoio Pedagógico Especializado (SAPE) com professores e gestores do ensino comum, equipe técnico-pedagógica. A versão final do manual contempla aspectos teórico-operacionais sobre os temas: flexibilização e adequação curricular, educação inclusiva, definição de NEEs, funcionamento do SAPE; e se encerra com uma proposta modelo de ACI. Espera-se que o uso do material subsidie o trabalho pedagógico dos professores na proposição curricular para alunos que se encontram muito distantes do nível acadêmico esperado.
Curricular adaptation: alternatives of pedagogical support in the inclusive education
Keywords: Adaptação currricular; adequações curriculares; Alunos com Necessidades Educacionais Especiais; Educação inclusiva; curriculo